Social work practice research for the twenty-first century - Fortune, Anne E.; McCallion, Philip; Briar-Lawson, Katharine (Columbia University Press, 2010)
Social work professionals must demonstrate their effectiveness to legislators and governments, not to mention clients and incoming practitioners. A thorough evaluation of the activities, ethics, and outcomes of social work practice is critical to maintaining investment and interest in the profession and improving the lives of underserved populations.Incorporating the concerns of a new century into a consideration of models for practice research, this volume builds on the visionary work of William J. Reid (1928-2003) who transformed social work research through empirically based and task-centered approaches-and, more recently, synthesized intervention knowledge for framing future study. This collection reviews the task-centered model and other contemporary Evidence-Based Practice models for working with individuals, families, groups, communities, and organizations. Essays demonstrate the value of these pragmatic approaches in the United States and international settings. Contributors summarize state-of-the-art methods in several key fields of service, including children and families, aging, substance abuse, and mental health. They also evaluate the research movement itself, outlining an agenda for today's sociopolitical landscape and the profession. This volume inspires practice research to prioritize evidence as a base for the profession.
Keywords: Social service : Research; Evaluation research (Social action programs)